PERANCANGAN SISTEM POMPA AIR DC DENGAN PLTS 20 kWp TIANYAR TENGAH SEBAGAI SUPLAI DAYA UNTUK MEMENUHI KEBUTUHAN AIR MASYARAKAT BANJAR BUKIT LAMBUH - Kadek Bayu Kusuma; Cok Gede Indra Partha; I Wayan Sukerayasa (Jurnal SPEKTRUM, 2020)
Karangasem Regency, especially in Kubu Subdistrict, Tianyar Tengah Village, Banjar BukitLambuh, is an area that still lacks clean water, so that villagers still rely on purchasing clean waterthrough tank trucks at high prices. Around Banjar Bukit Lambuh, there is a 20 kWp Central TianyarPLTS which has been abandoned since 2016 due to the absence of regional companies that manageand maintain the PLTS so that some components of the PLTS are damaged. The abandonment of the20 kWp PLTS makes the Bali Provincial Manpower and Energy Department (ESDM) Department planto transfer the function of PLTS as a source of electricity for water pumps that lift water fromreservoirs with a water capacity of 72,000 liters to a 30,000 liter water reservoir which is near thePLTS to meet the water needs of residents in the Middle Tianyar Village Banjar Bukit Lambuh. Theselected water pump type Lorentz PS2-4000 C-SJ3-32 submersible DC with a total head of 108.6meters and a pipe length of 1,640 meters and requires power of 2.96 kW supplied from PLTS 20 kWpTianyar Tengah with a cable length of 1,640 meters and voltage drop of 8,183 volts, so that the pumpcan operate for 7 hours with 4.2 m3 / h water discharge producing 29,400 liters of water that can meetthe water needs of residents of Banjar Bukit Lambuh Village by 23,328 liters per day.